2019
DOI: 10.1155/2019/7435248
|View full text |Cite
|
Sign up to set email alerts
|

Cold Pulsatile Machine Perfusion versus Static Cold Storage in Kidney Transplantation: A Single Centre Experience

Abstract: Introduction We present our experience with hypothermic machine perfusion (HMP) versus cold storage (CS) in relation to kidney transplant outcomes. Methods Retrospective analysis of 33 consecutive HMP kidney transplant outcomes matched with those of 33 cold stored: delayed graft function (DGF), length of hospital stay (LOS), estimated glomerular filtration rate (eGFR), and patient and graft survival were compared. Renal Resistive Indexes (RIs) during HMP in relation to DGF were also analysed. Results In the HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] identified by the systematic search were included into the analysis (Table 2); fifteen were published papers and seven were abstracts. Ten were RCTs [6,11,12,15,16,18,19,21,24,25], seven studies were retrospective [7,8,9,10,17,22,23], and five were prospective [13,14,20,26,27]. Predominantly, the studies used a LifePort ® kidney transporter for hypothermic machine preservation; there was a large variation in cold storage solution type, with some studies not mentioning the specific cold storage preservation solution, but instead referring to local guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] identified by the systematic search were included into the analysis (Table 2); fifteen were published papers and seven were abstracts. Ten were RCTs [6,11,12,15,16,18,19,21,24,25], seven studies were retrospective [7,8,9,10,17,22,23], and five were prospective [13,14,20,26,27]. Predominantly, the studies used a LifePort ® kidney transporter for hypothermic machine preservation; there was a large variation in cold storage solution type, with some studies not mentioning the specific cold storage preservation solution, but instead referring to local guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, a higher proportion of patients may suffer from early graft dysfunction or delayed graft function (DGF), prolonged hospital stay, and increased morbidity in general: Biliary complications in The insights and understanding behind the underlying molecular mechanisms of IRI are important for identification of suitable biomarkers and development of different novel reconditioning approaches such as small interfering RNA (siRNA), drug delivery for attenuating pro-apoptotic molecules, and downstream signalling pathways. These interventions could be adopted during MP to counteract damage due to IRI and reduction of the risk of post-transplantation DGF, one of the well-known clinical manifestations of IRI in transplanted grafts [8].…”
Section: Current State Of Abdominal Transplantation (Liver Kidneys mentioning
confidence: 99%
“…Prolonged ischaemic time is significantly detrimental to long-term survival for deceased donor grafts [20], with preservation strategies being key for suboptimal and extended criteria deceased donor organs [12]. Often 3rd and 4th kidney transplants are associated with prolonged ischaemic times due to increasing technical complexity: KTRs of 3rd and 4th transplants may have difficult vasculature that often requires additional surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delayed graft function in kidneys from deceased donors varies, but is overall as high as 30%; it might also take weeks before the recipient is fully dialysis independent [11,12], thus the recipients are more exposed and vulnerable in the post-operative period. Conversely, kidneys from living donors tend to function immediately, reducing the risk of hospitalisation and renal replacement therapy after transplant to less than 4% [13] and setting in this way the recipient for the best short-and long-term outcome.…”
Section: Introductionmentioning
confidence: 99%